2019
DOI: 10.1093/jbi/wbz045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shimming Techniques on MRI Breast Image Quality at 1.5T

Abstract: Objective The quality of all clinical MRI is dependent on B0 homogeneity, which is optimized during the shimming part of a prescan or preparatory phase before image acquisition. The purpose of this study was to assess shimming techniques clinically employed for breast MRI across our practice, and to determine factors that correlate with higher image quality for contrast-enhanced breast MRI at 1.5T. Methods One hundred consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Some scanners provide one additional shimming FOV for breast imaging; however, the variability of the parameter adjustment by the technologists is experience-dependent and can affect the shimming output and image quality significantly. 2 It is even more challenging to shim the two-voxel MRS for two breasts simultaneously. 42 The HAPLS approach can improve bilateral breast MRI/MRS significantly, although it will require different designs and optimizations for different applications and FOVs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some scanners provide one additional shimming FOV for breast imaging; however, the variability of the parameter adjustment by the technologists is experience-dependent and can affect the shimming output and image quality significantly. 2 It is even more challenging to shim the two-voxel MRS for two breasts simultaneously. 42 The HAPLS approach can improve bilateral breast MRI/MRS significantly, although it will require different designs and optimizations for different applications and FOVs.…”
Section: Discussionmentioning
confidence: 99%
“…A typical scan routine images the breasts sequentially, which is time‐consuming. Some scanners provide one additional shimming FOV for breast imaging; however, the variability of the parameter adjustment by the technologists is experience‐dependent and can affect the shimming output and image quality significantly 2 . It is even more challenging to shim the two‐voxel MRS for two breasts simultaneously 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequences of poor system settings can include incomplete water excitation, flip angle inaccuracy, image distortion, or fat suppression failure. For example, recent work by Zhou et al found a statistically significant relationship between the x, y, and z linear shims and the quality of fat suppression in breast MRI [ 4 ]. While their work focused on the linear shims, fat suppression quality relies on the totality of scan-specific system settings.…”
Section: Introductionmentioning
confidence: 99%
“…Manually aligning these volumes to the individual patient anatomy in all three dimensions is prone to error and intra- and inter-reader variability. The work by Zhou et al also highlighted the variability in pre-scan placement by clinical technologists and how that variability could impact scan-specific system settings and image quality [ 4 ].…”
Section: Introductionmentioning
confidence: 99%